2020
DOI: 10.3390/ma13112502
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Analysis of Half-Warm Asphalt Mixes Containing Electric Arc Furnace (EAF) Slag and Reclaimed Asphalt Pavement (RAP) Using a Novel Thermomechanical Healing Treatment

Abstract: Nowadays, the self-healing of asphalt pavements promoted by microwave radiation heating energy is gaining attention and strength in the scientific community. However, most of these studies are only conceptual and, thus, remain shrouded in uncertainty regarding technology development, economy, and application effect. Therefore, there are several efforts underway to offer more effective assisted healing treatments that are capable of overcoming such uncertainties. This paper aims to assess and quantify the heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Based on previous reports, around 190-290 million tons of steel slag are generated every year [4]. Most of the global steel slag ends up being disposed of, with only a small portion recycled [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Studies have also shown that the recycling rate of steel slag is still generally much lower in Asian countries [2,[21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous reports, around 190-290 million tons of steel slag are generated every year [4]. Most of the global steel slag ends up being disposed of, with only a small portion recycled [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Studies have also shown that the recycling rate of steel slag is still generally much lower in Asian countries [2,[21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Winkle's investigation results from laboratory and field evaluation showed that with an increasing RAP content, the stiffness of asphalt mixtures increased, while fracture energy decreased [16]. Besides, adding RAP also impacted negatively on the short-term and long-term aging behaviors of asphalt mixtures [17], in addition to the self-healing property [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the field, the thermomechanical treatment would be implemented by heating the deteriorated pavement with a MW generator and then re-compacting the pavement (27). The effectiveness of this technology was also assessed for Half-Warm Asphalt Mixes (HWMA) containing EAFS and Reclaimed Asphalt Pavement (RAP) (28).…”
Section: Introductionmentioning
confidence: 99%